2015
DOI: 10.1111/echo.13123
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Flow Reserve Predicts Longitudinal Myocardial Deformation Capacity in Heart‐Transplanted Patients

Abstract: HTx patients have reduced CFVR, exercise capacity, and LV longitudinal myocardial deformation capacity compared with healthy individuals. HTx patients with reduced CFVR are more symptomatic and have increased prevalence of CAV. Furthermore, reduced CFVR is correlated with reduced LV longitudinal myocardial deformation and exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Another main observation is a statistically significant correlation between CFVR and LVGLS (r = 0.4, p<0.0001), which is similar to that in a previous study (r = 0.8,P < 0.0001) [5]. Notably, the collinearity between LVGLS and CFVR cannot be ruled out strictly, which may affect the accuracy of the combined model.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 84%
“…Another main observation is a statistically significant correlation between CFVR and LVGLS (r = 0.4, p<0.0001), which is similar to that in a previous study (r = 0.8,P < 0.0001) [5]. Notably, the collinearity between LVGLS and CFVR cannot be ruled out strictly, which may affect the accuracy of the combined model.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 84%
“…CAC: coronary artery calcium; CAV: cardiac allograft vasculopathy; CCTA: cardiac computed tomography angiography; CMR: cardiac magnetic resonance; DS: dobutamine-stress ECD: echocardiography; GLS: global longitudinal strain: LVEF: left ventricular ejection fraction; MBF: myocardial blood flow; PET: positron emission tomography; SPECT: single-photon emission computed tomography; WMAs: wall motion abnormalities LV-GLS and the presence of CAV and coronary microvascular dysfunction (Fig. 3) [26][27][28]. Clemmensen et al found a statistically significant correlation, and a significant reduction of LV-GLS among patients with no and mild CAV (CAV 0 vs CAV 1 ), as well as a preserved LVEF even in presence of moderate-to-severe CAV [26].…”
Section: Wall Motion Abnormalitiesmentioning
confidence: 99%
“…Similar to reduced MPR by vCMR, abnormal global longitudinal strain (GLS) derived from transthoracic echocardiography (TTE) has been recently shown to be associated with CAV and coronary microvascular dysfunction [1517] in studies from a single group of investigators. Moreover, the same group has reported that decreased GLS is associated with repeated episodes of allograft rejection [18].…”
Section: Introductionmentioning
confidence: 99%